Evidence for a Third Visual Pathway Specialized for Social Perception - Pitcher, David; Ungerleider, Leslie G. (Trends in cognitive sciences, 2021)
Existing models propose that primate visual cortex is divided into two functionally distinct pathways. The ventral pathway computes the identity of an object; the dorsal pathway computes the location of an object, and the actions related to that object. Despite remaining influential, the two visual pathways model requires revision. Both human and non-human primate studies reveal the existence of a third visual pathway on the lateral brain surface. This third pathway projects from early visual cortex, via motion-selective areas, into the superior temporal sulcus (STS). Studies demonstrating that the STS computes the actions of moving faces and bodies (e.g., expressions, eye-gaze, audio-visual integration, intention, and mood) show that the third visual pathway is specialized for the dynamic aspects of social perception. The two-visual pathway model of primate visual cortex needs to be updated. We propose the existence of a third visual pathway on the lateral brain surface that is anatomically segregated from the dorsal and ventral pathways.The third pathway exists in human and non-human primates. In humans, the third pathway projects from early visual cortex into the superior temporal sulcus (STS). In macaques the third pathway projects from early visual cortex into the dorsal bank and fundus of the STS.The third pathway has distinct functional properties. It selectively responds to moving faces and bodies. Visual field-mapping studies show that the third pathway responds to faces across the visual field to a greater extent than the ventral pathway.The third pathway computes a range of higher sociocognitive functions based on dynamic social cues. These include facial expression recognition, eye gaze discrimination, the audiovisual integration of speech, and interpreting the actions and behaviors of other biological organisms.